PENINGKATAN KEMAMPUAN MENEMBAK DENGAN LATIHAN WALL SQUAD PADA ATLET MENEMBAK SILVER BULLET INDONESIA - Rochman, Zulfikar Habibur; Irawan, Roy Januardi (Kesehatan Olahraga, 2024)
The athletes in the Indonesian Silver Bullet shooting club who were observed experienced many obstacles, especially in strengthening the quadriceps muscles, particularly in the 18-41 m metallic silhouette PCP air rifle shooting class. This study aims to determine the effectiveness of wall training in improving shooting results in the 18-41 m metallic silhouette PCP air rifle shooting class at the Indonesian Silver Bullet club. This study is an experimental study with a research design of "Pretest-Posttest Control Group Design." The instrumentation technique and data collection method used were the results of shooting tests on athletes who did not receive wall training treatment compared to athletes who had received wall training treatment. The sample for this study was 30 Indonesian Silver Bullet athletes (15 children in the experimental group and 15 children in the control group). The data analysis technique used in this study was the t-test with a significance level of 0.073%. According to the results of the study, the experimental group showed a value of ? 0.05, while the control group showed a value of 0.190 and a Sig value (P value) of 0.153. The value and Sig (P value) are both ? 0.05. Therefore, it can be concluded that there is a significant difference between the experimental group and the control group in the results of the 18-41m shooting athletes in the Metallic Silhouette PCP category at the Silver Bullet Indonesia club if the P value is <0.05.